GASTRONOMI DAN WARISAN BUDAYA DI GADRI RESTORAN YOGYAKARTA - Dwi Santoso, Alek; Setiawan, Budi (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
Gastronomy is not only related to food but also serves as a representation of culture and local identity. This study aims to examine how Gadri Restaurant in Yogyakarta promotes traditional gastronomic values as part of cultural heritage preservation. Using a qualitative approach through observation, interviews, and literature review, the findings reveal that Gadri Restaurant Yogyakarta not only serves authentic Javanese cuisine but also embeds cultural narratives in its presentation, interior design, and interactions between staff and customers. The restaurant functions as both a space for cultural preservation and a medium for local gastronomic education for the community and tourists alike. Keywords: Gastronomy, Cultural Heritage, Gadri Restaurant, Javanese Cuisine